Investigation of heat transfer and exergy loss in oscillating circular pipes - Gul, H.; Akpinar, Ebru Kavak (Pergamon-Elsevier Science Ltd, 2007)
In this study, the effect on heat transfer rates, friction factor and exergy loss of oscillating pipe were investigated. Air was used as working, fluid. To obtain oscillating motion of the test pipe, the experimental setup was designed. Thermocouple, the temperature control system and the other measurement systems were installed on the oscillating section. For both steady and oscillating flows, the bulk and local wall temperature distribution, pressure drop, inlet and outlet temperatures and frequency were measured. The parameters for this study were chosen as Reynolds number from 5000 to 20,000 at oscillating frequencies with 10 and 20 Hz. The variations of Nusselt number and exergy loss with these parameters were determined and presented graphically. In oscillatory flow, a heat transfer enhancement of up to at constant pumping power was achieved. The exergy loss was decreased with the increase of Reynolds number. The exergy loss affected slightly from the increase of oscillating frequencies. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: heat transfer; oscillating flow; oscillatory frequency; Nusselt number; exergy loss